Extrusion of mitochondria: Garbage clearance or cell–cell communication signals?. Issue 5 (6th March 2022) - Lyamzaev, Konstantin G.; Zinovkin, Roman A.; Chernyak, Boris V.
Abstract: Mitochondria are dynamic organelles that regulate various intracellular signaling pathways, including the mechanisms of programmed cell death, differentiation, inflammation, and so on. Mitochondria may be extruded as membrane enveloped or as free organelles during developmental processes, inflammatory activation, and in the process of "garbage clearance" of damaged mitochondria in postmitotic cells. Extracellular mitochondria can be engulfed by immune and nonimmune cells and trigger intracellular signaling leading to an inflammatory response. At the same time, it was reported that the release of extracellular vesicles containing mitochondria from mesenchymal stem cells contributes to their therapeutic anti‐inflammatory effects. Numerous studies claim that engulfed mitochondria improve cellular bioenergetics, but this assumption requires further investigation. This review aims at a critical discussion of the mechanisms of mitochondrial extrusion in mammals, the reception of mitochondrial components, and the responses of recipient cells to extracellular mitochondria. Abstract : This review aims at a critical discussion of the mechanisms of mitochondrial extrusion in mammals, the reception of mitochondrial components, and the responses of recipient cells to extracellular mitochondria.